Peningkatan Profesionalisme Guru Madrasah Ibtidaiyah Miftahul Huda 2 Palangka Raya Melalui Pelatihan Kurikulum 2013 - Asmawati, Asmawati; Rizal, Setria Utama; Sulistyowati, Sulistyowati (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this agenda is to increase teacher professionalism in implementing learning through 2013 curriculum training at Madrasah Ibtidaiyah Miftahul Huda 2 Palangka Raya. The service method used is lecture, question and answer, discussion, practice and mentoring. The results of the activity show that the increasing ability and insight of the Madrasah Ibtidaiyah Miftahul Huda 2 Palangka Raya teachers is related to the implementation of the 2013 curriculum and increases the knowledge and skills of the Madrasah Ibtidaiyah Miftahul Huda 2 Palangka Raya teachers on how to implement learning in the 2013 curriculum both in terms of planning, implementation and evaluation.